INHERENT CHARACTERISTICS ANALYSIS OF GRAPHENE REINFORCED CONICAL SHELLS WITH ARBITRARY BOUNDARY CONDITIONS - JIA WeiGe (Jixie qiangdu)
This paper investigated inherent characteristics of graphene reinforced conical shells with arbitrary boundary conditions based on Love shell theory. The mechanics model for graphene reinforced composites and the free vibration differential equation of graphene reinforced conical shells were deduced. Finally, parameter studies were carried out to evaluate effects of boundary conditions and material and geometric parameters on inherent characteristics of conical shells.